2000
DOI: 10.1590/s1517-83822000000400001
|View full text |Cite
|
Sign up to set email alerts
|

Survival and conjugal transfer between Bacillus thuringiensis strains in aquatic environment

Abstract: Field and laboratory studies were conducted to assess the survival of cells and spores and plasmid transfer between Bacillus thuringienis strains in aquatic environment. Results indicated that cells and spores of B. thuringiensis can survive for 10 days in water, without altering their number. The sporulation process began after 12-15 hours of inoculation of water. B. thuringiensis was able to transfer conjugative plasmids in the aquatic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…thuringiensis ecological studies try to determine under which environmental conditions cells and insecticidal protein are most active. This study confirmed that although a large number of spores is released in the environment to control insect pests, survival and multiplication do not occur (Furlaneto et al, 2000;Ohana et al, 1987;Thomas et al, 2000;2001;Vilas-Bôas et al, 2000). It also shows that the decline in extractable Cry protein from the environment might be related to its adsorption to soil particles.…”
Section: Toxin Persistence In Soilsupporting
confidence: 77%
“…thuringiensis ecological studies try to determine under which environmental conditions cells and insecticidal protein are most active. This study confirmed that although a large number of spores is released in the environment to control insect pests, survival and multiplication do not occur (Furlaneto et al, 2000;Ohana et al, 1987;Thomas et al, 2000;2001;Vilas-Bôas et al, 2000). It also shows that the decline in extractable Cry protein from the environment might be related to its adsorption to soil particles.…”
Section: Toxin Persistence In Soilsupporting
confidence: 77%
“…But the multiplication and conjugation of B. thuringiensis reach high indexes in dead insects' larvae (31). Also, the persistence of B. thuringiensis in the water have allowed us to notice that, in laboratory experiments, the cells and the spores can remain up to 10 days in this medium, with sporulation beginning between 12 and 15 hours after inoculation (16). In this context we advise the carrying out of field assays with the B. thuringiensis isolates used in this research, which can be useful in a biofungicidal formula similar to the work carried out by Vidhyasekaran et al (34), who used Pseudomonas fluorescens to control Bacillus oryzae, with an activity equivalent to the chemical fungicide, which allowed for an increase in rice production.…”
mentioning
confidence: 99%
“…Taking into account that the ecological role of B. thuringiensis in the environment is poorly understood, many studies with this subject were conducted aiming to know the behavior of B. thuringiensis in soil, water, insects and foodstuffs (Pruett et al 1980;Petras and Casida 1985;Ohana et al 1987;Thomas et al 2000Thomas et al , 2001Furlaneto et al 2000;Vilas-Bôas et al 2000;Ferreira et al 2003; Van der Auwera et al 2007;Modrie et al 2010;Santos et al 2010). Thus, Aly et al (1985) were the first authors to demonstrate spore germination, sporulation and toxin production of B. thuringiensis subsp.…”
Section: Conjugation As a Tool Tomentioning
confidence: 99%
“…Furlaneto et al (2000) evaluated the survival and conjugal transfer between B. thuringiensis strains in aquatic environment. The detected frequencies of conjugal transfer were low since this environment does not support vegetative cell multiplication allowing the spores formation rapidly.…”
Section: Conjugation As a Tool Tomentioning
confidence: 99%